Benchmarking biomarker‐based criteria for Alzheimer's disease: Data from the Swedish Dementia Registry, SveDem. Issue 12 (13th June 2015) - Rosén, Christoffer; Farahmand, Bahman; Skillbäck, Tobias; Nägga, Katarina; Mattsson, Niklas; Kilander, Lena; Religa, Dorota; Wimo, Anders; Blennow, Kaj; Winblad, Bengt; Zetterberg, Henrik; Eriksdotter, Maria
Abstract: Introduction: New research guidelines for the diagnosis of Alzheimer's disease (AD) include biomarker evidence of amyloid‐β (Aβ) and tau pathology. The aim of this study was to investigate what proportion of AD patients diagnosed in clinical routine in Sweden that had an AD‐indicative cerebrospinal fluid (CSF) biomarker profile. Methods: By cross‐referencing a laboratory database with the Swedish Dementia Registry (SveDem), 2357 patients with data on CSF Aβ and tau biomarkers and a clinical diagnosis of AD with dementia were acquired. Results: Altogether, 77.2% had pathologic Aβ42 and total tau or phosphorylated tau in CSF. These results were stable across age groups. Female sex and low mini‐mental state examination score increased the likelihood of pathologic biomarkers. Discussion: About a quarter of clinically diagnosed AD patients did not have an AD‐indicative CSF biomarker profile. This discrepancy may partly reflect incorrect (false positive) clinical diagnosis or a lack in sensitivity of the biomarker assays.